Selective Permeable Lithium‐Ion Channels on Lithium Metal for Practical Lithium–Sulfur Pouch Cells - Chen, Peng‐Yu; Yan, Chong; Chen, Pengyu; Zhang, Rui; Yao, Yu‐Xing; Peng, Hong‐Jie; Yan, Li‐Tang; Kaskel, Stefan; Zhang, Qiang (Angewandte Chemie International Edition, 2021)
Lithium metal batteries are considered a promising candidate for high‐energy‐density energy storage. However, the strong reducibility and high reactivity of lithium lead to low Coulombic efficiency when contacting oxidants, such as lithium polysulfide caused by the serious “shuttle effect” in lithium–sulfur batteries. Herein we design selectively permeable lithium‐ion channels on lithium metal surface, which allow lithium ions to pass through by electrochemical overpotential, while the polysulfides are effectively blocked due to the much larger steric hindrance than lithium ions. The selective permeation of lithium ions through the channels is further elucidated by the molecular simulation and visualization experiment. Consequently, a prolonged cycle life of 75 cycles and high Coulombic efficiency of 99 % are achieved in a practical Li–S pouch cell with limited amounts of lithium and electrolyte, confirming the unique role the selective ion permeation plays in protecting highly reactive alkali metal anodes in working batteries. Selectively permeable lithium‐ion channels, which were created by aminopropyl‐terminated polydimethylsiloxanes anchored on the lithium metal surface, allow lithium ions to get through, while the polysulfides are effectively blocked due to their much larger volume. The selective lithium ion channels enable a prolonged cycle life and a high Coulombic efficiency of 99 % in a practical Li–S pouch cell.